The analysis of clinical course and outcome of soft tissue sarcoma in parameningeal localization in children treated according to the CWS 96 protocol – a report of the Polish Paediatric Solid Tumours Group - Zalewska-Szewczyk, Beata; Kazanowska, Bernarda; Młynarski, Wojciech; Dłużniewska, Agnieszka; Drożyńska, Elżbieta; Kurylak, Andrzej; Nurzyńska-Flak, Joanna; Rybczyńska, Aleksandra; Pietniczka-Załęska, Mirosława; Rychłowska-Pruszyńska, Magdalena; Solarz, Elżbieta; Wieczorek, Maria; et al. (Contemporary Oncology/Współczesna Onkologia, 2008)
Aim of the study: The aim of the study was to evaluate clinical course and treatment outcome in children with soft tissue sarcomas (STS) in parameningeal localization, treated in the centres of the Polish Paediatric Solid Tumours Group in years 1996-2002, according the protocol CWS 96. Material and methods: One hundred and forty-one children were enrolled in the study; 28 (13.9%) of them had parameningeal tumours. The clinical course and outcome were analyzed, with regard to the gender, age at the onset of the disease, the number of the afflicted anatomical structures, extent of the disease, histology, the kind of chemotherapy (VAIA vs. CEVAIE), surgery and radiotherapy. Results: Parameningeal STS occurred significantly more often in boys (p=0.03). The afflicted lymph nodes and the presence of metastases did not influence the frequency of treatment failures. There was no influence of the histology or the kind of chemotherapy (VAIA vs. CEVAIE) on the clinical outcome. However, higher frequency of relapses and deaths in children with delayed radiotherapy was observed (p=0.09 and p=0.2). Parameningeal localization of STS was significantly associated with worse DSF (parameningeal tumours 56.4% vs. non-parameningeal tumours 71.3%; p=0.02), and ESF (60% vs. 78%, p=0.012). Conclusions: The most important therapeutic option in soft tissue sarcomas in parameningeal localization is local therapy, especially radiotherapy. There is low probability of microscopic radical resection of the tumour in these tumours. Favourable histology is not a good prognostic factor in parameningeal soft tissue sarcomas.